Kebiasaan Tidak Menggunakan Helm di Kalangan Pengguna Kendaraan Bermotor Roda Dua di Jalan Ahmad Yani, Km. 4,5 Banjarmasin Timur - Nourfah, Syarifah; Alfisyah, Alfisyah; Mattiro, Syahlan (Universitas Lambung Mangkurat, 2024)
The purpose of this study is to see: (1) describe the causes of two-wheeled motor vehicle users not wearing helmets on street Ahmad Yani, KM 4.5 East Banjarmasin. (2) describes traffic perceptions among two-wheeled motor vehicle users who do not use helmets on street Ahmad Yani, KM 4.5 East Banjarmasin. This study uses a qualitative method. incidental sampling used in the selection of data sources and informants in this study amounted to 14 people. The data collection techniques used were observation, interviews and documentation. The data analysis technique used in this study was data reduction, data presentation and conclusion drawing. The results of this study indicate the reason that two-wheeled motorized vehicle users are accustomed to not wearing a helmet, namely the trip is quite close and there is no ticket from the SATLANTAS officers. Perceptions of traffic violations among users of two-wheeled motorized vehicles who do not use helmets, namely deliberately not wearing helmets and not having any warning from traffic officers